2009
DOI: 10.1371/journal.pcbi.1000452
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model of Trp-Cage Folding from Multiple Biased Molecular Dynamics Simulations

Abstract: Trp-cage is a designed 20-residue polypeptide that, in spite of its size, shares several features with larger globular proteins. Although the system has been intensively investigated experimentally and theoretically, its folding mechanism is not yet fully understood. Indeed, some experiments suggest a two-state behavior, while others point to the presence of intermediates. In this work we show that the results of a bias-exchange metadynamics simulation can be used for constructing a detailed thermodynamic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
413
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 272 publications
(441 citation statements)
references
References 82 publications
28
413
0
Order By: Relevance
“…In addition, these findings corroborate with the recent IR experiment of Meuzelaar et al 19 Interestingly enough, we found that the intermediate I state, consisting of a formed α-helix with a solvated and 24,28 We can solve this paradox, by constructing the free energy landscape.…”
Section: The Stationary Distribution or Equilibrium Populationsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, these findings corroborate with the recent IR experiment of Meuzelaar et al 19 Interestingly enough, we found that the intermediate I state, consisting of a formed α-helix with a solvated and 24,28 We can solve this paradox, by constructing the free energy landscape.…”
Section: The Stationary Distribution or Equilibrium Populationsupporting
confidence: 91%
“…They found Trp-cage folding paths that formed tertiary contacts and the salt bridge before formation of the helix, as well as paths that first formed the helix. These two folding routes were also observed by Marinelli et al 24 using bias exchange metadynamics simulations. These authors calculated that the folding process takes ∼2.3 ± 0.7 μs.…”
Section: Introductionsupporting
confidence: 77%
“…3A). Specifically, we employed the bias-exchange metadynamics (BE) method (26)(27)(28), to derive quantitative information on the conformational freedom of the protein, in the form of free-energy landscapes (see Materials and Methods). BE simulations were thus carried out for wild-type TeaA, in the apo and substrate-bound states.…”
Section: Resultsmentioning
confidence: 99%
“…The probability of the on state is the integral of this 2D function for 0 < RMSD 2 < 4 Å and 6 < RMSD 1 < 10 Å, whereas for the off state is 0 < RMSD 1 < 4 Å and 6 < RMSD 2 < 10 Å. Error estimates were computed as described previously (52).…”
Section: Methodsmentioning
confidence: 99%